The Police's Effort in Commanding Criminal Acts of Violence in Football Champion - Satria Diaz Pratama Putra Pratama Putra; Eko Soponyono (Jurnal Daulat Hukum, 2022)
Cases of violent criminal acts that occurred during football champion in Wonosobo Regency were found in the Wonosobo District Court Decision with case register number 117/Pid.B/2020/PN.WSB with imprisonment for each of 5 (five) months. The method used is juridical empirical research, descriptive research specifications, data sources obtained through secondary and primary data, data collection by literature study and interviews or interviews, qualitative data presentation methods and qualitative data analysis. Based on the results of the study, it was concluded that the panel of judges paid attention to the legal facts as stated in Article 170 paragraph (1) 1 of the Criminal Code, whose elements are: First, the element "whoever", second "openly and collectively", third "using violence against people or goods". Countermeasures by the Wonosobo Police are carried out with penal efforts, namely making arrests, subsequent investigations by transferring the completed case files to the Wonosobo District Attorney for further delegating the case to the Wonosobo District Court for trial. The implementation of non-penal efforts is to coordinate with the organizing committee and carry out escorts during football champion.